2016
DOI: 10.1002/jssc.201600617
|View full text |Cite
|
Sign up to set email alerts
|

Target-guided isolation of polar antioxidants fromAbelmoschus esculentus(L). Moench by high-speed counter-current chromatography method coupled with wavelength switching and extrusion elution mode

Abstract: An off-line two-dimensional high-speed counter-current chromatography strategy combined with the wavelength switching technique and extrusion elution mode was successfully developed and applied to the isolation of polar antioxidants from Abelmoschus esculentus (L).Moench. Target-guided by the result of 2,2-diphenyl-1-picrylhydrazyl screening assay, four antioxidants were obtained with purities over 90% through orthogonal high-speed counter-current chromatography separation. UV spectroscopy, mass spectrometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Most compounds tested in the plasma have been reported to exert anti-inflammatory (for KSG and KS), antioxidant (for QS and KS), and hepatoprotective effects (for KG). KF displays several pharmacological properties, such as antimicrobial, anti-inflammatory, antioxidant, antitumor, cardioprotective, neuroprotective, and antidiabetic activities [58][59][60][61][62][63]. Some biological activities of the compound may also be attributed to the antihyperuricemic activity of the SFB flavonoid extract.…”
Section: Pharmacokinetic Parameters Of Phase-ii Metabolitesmentioning
confidence: 99%
“…Most compounds tested in the plasma have been reported to exert anti-inflammatory (for KSG and KS), antioxidant (for QS and KS), and hepatoprotective effects (for KG). KF displays several pharmacological properties, such as antimicrobial, anti-inflammatory, antioxidant, antitumor, cardioprotective, neuroprotective, and antidiabetic activities [58][59][60][61][62][63]. Some biological activities of the compound may also be attributed to the antihyperuricemic activity of the SFB flavonoid extract.…”
Section: Pharmacokinetic Parameters Of Phase-ii Metabolitesmentioning
confidence: 99%
“…It is a novel technology which is based on multistage extraction system [12,13]. No irreversible adsorption, high recovery, and a large loading make HSCCC widely applicable to the isolation of compounds from natural products [14–17]. However, sometimes it is challenging to find a perfect solvent system to perform in high purity in a one‐step separation by HSCCC.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the purities of the final products are poor. In recent years, many modern separation techniques have been employed in the isolation of flavonoid glycosides from TCMs, such as high‐speed counter‐current chromatography . Although this approach affords high‐separation efficiency, separations take hours.…”
Section: Introductionmentioning
confidence: 99%
“…Modern studies have demonstrated that the major bioactive components of S. salsula are flavonoid glycosides [1,2]. Flavonoid glycosides have many biological functions, including anti-hepatitis [3], [9][10][11]. Although this approach affords high-separation efficiency, separations take hours.…”
Section: Introductionmentioning
confidence: 99%